The consequences of the FASB's 1998 proposal on accounting for stock option repricing - Carter, Mary Ellen; Lynch, Luann J. (Journal of Accounting and Economics, 2003)
We examine repricing activity surrounding the FASB's 1998 announcement regarding accounting for repriced options. We find that repricing increases during, and decreases after, the 12-day window between the announcement and proposed effective dates, consistent with firms timing repricings to avoid recording an expense. We find that firms experiencing increasing earnings patterns, firms with earnings around zero, and growth firms are more likely to reprice in the window, but having repriced recently decreases the likelihood of doing so. The evidence suggests that firms trade off financial reporting benefits against reputation costs in decisions to time repricings to get favorable accounting treatment.